Genetic predisposition to altered blood cell homeostasis is associated with glioma risk and survival - Linda Kachuri; Geno A. Guerra; Taishi Nakase; George A. Wendt; Helen M. Hansen; Annette M. Molinaro; Paige Bracci; Lucie McCoy; Terri Rice; John K. Wiencke; Jeanette E. Eckel-Passow; Robert B. Jenkins; et al. (Nature Communications)
Abstract Glioma is a highly fatal and heterogeneous brain tumor with few known risk factors. Our study examines genetically predicted variability in blood cell indices in relation to glioma risk and survival in 3418 cases and 8156 controls. We find that increased platelet to lymphocyte ratio (PLR) confers an increased risk of glioma (odds ratio (OR) = 1.25, p = 0.005), especially tumors with isocitrate dehydrogenase (IDH) mutations (OR = 1.38, p = 0.007) and IDHmut 1p/19q intact (IDHmut-intact OR = 1.53, p = 0.004) tumors. Genetically inferred increased counts of lymphocytes (IDHmut-intact OR = 0.70, p = 0.004) and neutrophils (IDHmut OR = 0.69, p = 0.019; IDHmut-intact OR = 0.60, p = 0.009) show inverse associations with risk, which may reflect enhanced immune-surveillance. Considering survival, we observe higher mortality risk in patients with IDHmut 1p/19q with genetically predicted increased counts of lymphocytes (hazard ratio (HR) = 1.65, 95% CI: 1.24–2.20), neutrophils (HR = 1.49, 1.13–1.97), and eosinophils (HR = 1.59, 1.18–2.14). Polygenic scores for blood cell traits are also differentially associated with 17 tumor immune microenvironment features in a subtype-specific manner, including signatures related to interferon signaling, PD-1 expression, and T-cell/Cytotoxic responses. Our findings highlight immune-mediated susceptibility mechanisms with potential disease management implications.